Labour-use efficiency of rice farmers in Nigeria’s north-central region - Sadiq, Mohammed Sanusi (2022)
A cross sectional data collected through a structured questionnaire coupled with an interview schedule from 360 rice farmers selected via multi-stage sampling technique was used to determine the labour efficiency of rice farmers in Nigeria’s North-Central region. Both descriptive and inferential statistics were used to analyze the 2020 cropping season data. The empirical evidences showed a farming population that is gender bias due to stereotypes, that affected women access to and control over productive resources. Besides, economic-productive people that explored pecuniary advantages in order to achieve economies of scale engaged in cultivation of thinly uneconomic holdings. The poor economic status of the farm families made most of the farmers to rely on family labour for farm operations, thus keeping most of their children and young ones out of school. Furthermore, most of the farmers were fairly efficient in the use of labour with little technical support required to enable them achieve optimum labour efficiency level (frontier point). However, the empirical evidences showed competition for labour demand between farm and off-farm activities and conservative and complacency attitudes due to longevity in the enterprise to be the factors that affected labour efficiency. Therefore, the study calls for gender mainstreaming in agricultural budget to overcome women’s challenge on productive resources; incentivized the enterprise viz., credit provision; adoption of bottom-to-top approach in research and practical demonstration approach in transfer of innovative rice technologies.